Evaluation the Trade Decision-Making In the European Union In Terms of Resolving Commercial Disputes: An analysis of trade decision-making in the European Union (Journal of Advances and Scholarly Researches in Allied Education, 2016)
European Union since itsinception has been struggling to evolve a Decision making mechanism on Tradeissue. Over the years much deliberations has taken place on this issue amongmember states. The entry of new members particularly from East European andBaltic States with a different system of decision making in trade issues hascomplicated the problem. There has been no single pattern of EU decision makingin European Union. The primary focus has been to arrive at decision on tradeand commercial issue through negotiations and consensus.  The states always ensure that their nationaleconomic interests are preserved and protected while framing rules andregulations. In this paper an effort has been made understand and evaluate the processof trade decision making in European Union.